Preparation and photocatalytic performance of SiO2@Cu core–shell catalyst. Issue 2 (June 2015) - Su, Ge; Lin, Zhenzhen; Qi, Xinying; Zhu, Guoben; Liu, Wei; Cao, Lixin
Graphical abstract: Highlights: Synthesized SiO2 @Cu core–shell particles show good photocatalytic activity. Decolorization efficiency up to 97% for methyl violet was reached. XPS spectrum and element mapping confirm the shell composition (Cu/CuO). Apparent rate constant k MV is 9.75 times as high as k MB . Forming process and photocatalytic mechanism of SiO2 @Cu particles were proposed. Abstract: Cu is usually used as a metal catalyst in chemical industry and sewage treatment. This work revealed its potential application as a photocatalyst. Heterogeneous deposition–precipitation was adopted to prepare SiO2 @Cu catalyst. Products were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and energy dispersive spectrometer (EDS). It was found that the main component of the shell is Cu. Only a little Cu was oxidized into CuO. The formation process of the SiO2 @Cu core–shell structure was expounded. Photocatalytic activity of the catalyst was examined and explained through the decolorization of three organic dyes. The decolorization rate of methyl violet reached up to 97% after UV irradiation for 3 h. While, for methylene blue, it is relatively low. The reason for the selective decolorization was analyzed according to our proposed photocatalytic mechanism. The important action of Cu during the photocatalytic process is confirmed.